INSIGHTS ON THE EXPLORATION OF FOOD CULTURE OF TWO PROVINCIAL PLACES IN THE PHILIPPINES - Louie Galvez Giray; Loraine Cerillo; Bien Justine Cruz (TRIBUTE: JOURNAL OF COMMUNITY SERVICES, 2021)
This manuscript is compilation of insights on the food culture of Malolos, Bulacan and Mexico, Pampanga in the Philippines. The paper discusses factors that affect the food cultures in the said places. The paper has three major parts: (1) food as a social symbol; (2) food diversity; and (3) food history. The researchers resulted into a conclusion that the food cultures of Malolos, Bulacan and Mexico Pampanga have their own characteristics, especially in terms of the taste, but also share some similarities in terms of food preparation and some of its origins and symbols. These aspects were all affected by different factors such as foreign colonization, scarcity of food, availability of resources, religious beliefs, adaptability of the people in the current situation and innovation.